EKSPERIMEN SISTEM INTERLOCKING SELF-SUSTAINED PADA RECONFIGURABLE FLAT PACK FURNITURE - Marwan Noer; Mesah Sejati (Narada : Jurnal Desain dan Seni, 2019)
Flat-Pack furniture and interlocking systems are two terms that have very close links in today's modern furniture manufacturing industry. Where the combination of these two elements can provide many solutions in the creation of a versatile furniture product which is the focus of attention at this time. The self-sustained interlocking system as one of the elements in making flat-pack furniture has an essential function and significant influence in making a flat-pack furniture product that is not only multifunctional and ergonomic but also has a major role in producing environmentally friendly products. Since the invention of CNC router machine and laser cutting technology and the development of digital engineering software, this self-sustained interlocking system is known to be complex has developed very rapidly, and has produced many reconfigurable, multi-functional flat-pack furniture products with environmentally friendly characteristics at production costs makes sense.The research aims to review modern types of interlocking joints and try to explore and explore and find new approaches in making interlocking systems that are appropriate for Reconfigurable Flat Pack Furniture applications.